Mechanisms of mast seeding: resources, weather, cues, and selection. Issue 3 (1st August 2016) - Pearse, Ian S.; Koenig, Walter D.; Kelly, Dave
Summary: Mast seeding is a widespread and widely studied phenomenon. However, the physiological mechanisms that mediate masting events and link them to weather and plant resources are still debated. Here, we explore how masting is affected by plant resource budgets, fruit maturation success, and hormonal coordination of cues including weather and resources. There is little empirical support for the commonly stated hypothesis that plants store carbohydrates over several years to expend in a high‐seed year. Plants can switch carbohydrates away from growth in high‐seed years, and seed crops are more probably limited by nitrogen or phosphorus. Resources are clearly involved in the proximate mechanisms driving masting, but resource budget (RB) models cannot create masting in the absence of selection because some underlying selective benefit is required to set the level of a 'full' seed crop at greater than the annual resource increment. Economies of scale (EOSs) provide the ultimate factor selecting for masting, but EOSs probably always interact with resources, which modify the relationship between weather cues and reproduction. Thus, RB and EOS models are not alternative explanations for masting – both are required. Experiments manipulating processes that affect mast seeding will help clarify the physiological mechanisms that underlie mast seeding. Contents Summary 546 I. Introduction 546 II. Ultimate and proximate hypotheses for masting behaviour 547 III. The role of plant resources in masting 548 IV. Which resources limit seed set? 552 V. Pollination, fruit development, and masting 554 VI. Hormonal control of seed set and masting 556 VII. Evolutionary perspectives on masting behaviour 558 VIII. Unifying resource budget and economy of scale models of masting 558 IX. Conclusions 559 Acknowledgements 559 References 559